Viimeinen tuomio - Sinclair, Upton, 1878-1968 (Salt Lake City, UT : Project Gutenberg, 2016)
"Viimeinen tuomio" by Upton Sinclair is a socio-political treatise written during the early 20th century. This book addresses social injustices and economic disparities within American society, particularly focusing on the struggles faced by the working class. It presents a critique of capitalism, illustrating how wealth and power are concentrated in the hands of a few while the majority suffers from poverty and exploitation. In "Viimeinen tuomio," Sinclair examines the harsh realities of labor conditions in industries, particularly in Chicago's garment sector, where employees work long hours for meager wages. Through a series of arguments and examples, he highlights the struggle for survival faced by workers, including women and children, who are trapped in a cycle of low pay and exploitation. He invokes historical parallels, connecting the plight of workers to larger themes of revolution and social change, suggesting that a drastic restructuring of the economic system is necessary to achieve equality and fairness for all. Ultimately, Sinclair advocates for socialism as a means to redistribute wealth and empower the working class, emphasizing that true democratic governance cannot exist without economic equality. (This is an automatically generated summary.)
Release date is 2016-12-04
E-text prepared by Tapio Riikonen
Keywords: Socialism; United States -- Social conditions -- 1865-1918; United States -- Economic conditions -- 1865-1918